The influence of Information Management Capability on Companies’ Sustainable Competitive Advantage: A Multiple-Case Study of Brazilian Market-Leading Companies - Gastaud Maçada, Antonio Carlos; Brinkhues, Rafael Alfonso; Silva Freitas Jr., José Carlos da (Review of Business Management, 2020)
Purpose – The aim of this study is to assess the influence of Information Management Capability (IMC) on Companies’ Sustainable Competitive Advantage (SCA) based on the qualitative approach. Design/methodology/approach – This study presents results of a multiple-case study carried out in three leading companies in their sector in Brazil (a credit union, a fashion retailer, and a furniture manufacturer). Findings –The results point towards a series of connections between Information System capacities (information management and integration) and organizational capacities (flexibility, reconfigurations, and agility), which were observed through content analysis applied to the inter-occurrence of intermediate categories of these capacities. Originality/value – The strategic impact of information technology resources and capacities remains a source of controversy in the literature. This study contributes to the literature on Information Systems Management and Sustainable Competitive Advantage (SCA). These are influenced by resources and abilities related to information rather than just technological resources.